Synthesis, characterization and in vitro antimicrobial and anti‐breast cancer activity studies of metal complexes of novel pentadentate azo dye ligand. (14th July 2016) - Mahmoud, Walaa H.; Sayed, Fatma N.; Mohamed, Gehad G.
Abstract : A new azo dye with N3O2 donor set of atoms has been synthesized viacoupling reaction of 2, 6‐diaminopyridine with p ‐methoxybenzaldehyde. The molecular and electronic structure of the azo dye ligand (L) was optimized theoretically and the quantum chemical parameters were calculated. Molecular docking was used to predict the binding between L and the receptors of breast cancer mutant 3hb5‐oxidoreductase, crystal structure of Escherichia coli (3 T88) and crystal structure of Staphylococcus aureus (3q8u). The newly synthesized L was used for complex formation with Cr(III), Mn(II), Fe(III), Co.(II), Ni(II), Cu(II), Zn(II) and Cd(II) ions. The nature of bonding and the stoichiometry of L and its mononuclear complexes were deduced from elemental analyses, spectroscopic, magnetic susceptibility, molar conductance, electron spin resonance and conductivity measurements, thermogravimetric analyses and powder X‐ray diffraction. Elemental analysis data show that the complexes have composition of ML type with an octahedral geometry for all the complexes. The activation thermodynamic parameters were calculated. The prepared azo dye and its metal complexes were tested against various Gram‐positive and Gram‐negative bacteria and a fungus. Most complexes exhibit antibacterial and antifungal activities against these organisms. Anticancer evaluation studies against standard breast cancer cell line were performed using various concentrations. The activity index was calculated. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Anticancer activity of azo dye ligand (L) and its complexes.